Microrchidia CW-Type Zinc Finger 2, a Chromatin Modifier in a Spectrum of Peripheral Neuropathies - Jacquier, Arnaud; Roubille, Simon; Lomonte, Patrick; Schaeffer, Laurent (Frontiers in Cellular Neuroscience, 2022)
Microrchidia CW-type zinc finger 2 (MORC2) gene encodes a protein expressed in all tissues and enriched in the brain. MORC2 protein is composed of a catalytic ATPase domain, three coil-coiled domains allowing dimerization or protein complex interaction, a zinc-finger CW domain allowing DNA interaction, and a CHROMO-like (CHRromatin Organization Modifier) domain. Recently, de novo or dominantly inherited heterozygous mutations have been associated with a spectrum of disorders affecting the peripheral nervous system such as the Charcot-Marie-Tooth disease, spinal muscular atrophy-like phenotype disorder, or a neurodevelopmental syndrome associated with developmental delay, impaired growth, dysmorphic facies, and axonal neuropathy (DIGFAN). In this review, we detail the various mutations of MORC2 and their consequences on clinical manifestations. Possible genotype-phenotype correlations as well as intra and inter-family variability are discussed. MORC2 molecular functions such as transcriptional modulation, DNA damage repair, and lipid metabolism are then reviewed. We further discuss the impact of MORC2 mutations on the epigenetic landscape in the neuromuscular system and hypothesize probable pathophysiological mechanisms underlying the phenotypic variability observed.